PEMBERDAYAAN PROGRAM KELOMPOK USAHA BERSAMA (KUBe) di DESA MEDAN SENEMBAH KABUPATEN DELI SERDANG - Ardhansyah Putra Hrp; Julianto Hutasuhut; Dwi Saraswati (Politeknik Negeri Sriwijaya, 2020)
The purpose of this community service activity is to form a Joint Business Group (KUBE) for small businesses and included in underprivileged communities in Medan Senembah by providing creativity training as a media for business opportunities and conducting business assistance. The benefits of this activity are expected to foster an entrepreneurial spirit for the poor through the formation of joint business groups, empowering the potential of poor people, especially mothers, in increasing family income through increasing creative economic ventures and increasing local economic income and the region in general.The methods used in this activity are : (1) Focus Group Discussion (FGD) for the initial evaluation phase to know the potential of participants in making a product that will be used as a business medium; (2) Lecture method for the KUBE program socialization stage; (3) Demonstration method for the product manufacturing skills training stage